The Family Under the Bridge - Natalie Savage, Carlson; Nang ChanYeema (New York, United State Scholastic Inc., 1986)
Grumpy Armand, who lives under a bridge, finds himself with a ready-made family of children that he grows to love. He finds them a better home than under the bridge.
Keywords: Story Collection